Analysis of poverty level among timber millers in Osogbo Agricultural Zone of Osun State, Nigeria - Ganiyu, M. O; Fanifosi, G. E; Ariyo, C. A. (The Nigerian Journal of Rural Extension and Development, 2023)
Poverty continues to mull over from one generation to another and currently worsen among the rural dwellers than expected. Although, past government has adopted different programme to tackle poverty, but its intensity keeps increasing day-by-day. This study was therefore conducted to analyzed poverty status among timber millers (sawnwood producers) in Osogbo Agricultural Zone of Osun State. A multistage sampling procedure was used to select 90 respondents. Primary data (on socioeconomic characteristics, the annual income and expenditure faced by timber millers, source of credits and raw timbers as well as the mode/condition of living of the respondents) were collected with the aid of structured questionnaire supplemented with oral interview. Data were analyzed using descriptive statistics, Logistic regression model and Foster Greer Thorbecke (FGT) poverty index. Results reveal hat 62.2% of the respondents were male household heads with the mean age of 48years, 88.9% of the respondents were married and had a household size of 5 persons on average. Most of the timber millers in the area were largely literate, 72.2% were primarily into sawn-wood or timber milling enterprise and they depend mostly on cooperative loans for finance. The poverty aversion parameter values for poverty incidence (P0), poverty depth (P1) and poverty severity (P2) were 44.5%, 28.3% and 21.6%, respectively. This indicates that the poverty incidence was about 45%, the depth of poverty was 28.3% while the poverty severity was 21.6% among the respondents in the area. The study shows that meal skipping (35.4%), having low cost meal (24.3%), reducing meal size (15.4%), fasting (13.2%), borrowing from neighbours (8.1%), hunting and harvesting of fresh fruits from bush (3.7%) were the main coping strategies employed by the respondents in the study area to lessen the impact of poverty syndrome. The marginal effect from Logit estimate reveals that age of the respondents (P= 0.046), access to credit (P=0.011) and revenue generated from timber milling business (P=0.000) significantly determined poverty level among the respondents in the study area. However, significant numbers of timber millers (45%) are poor and if credit facilities should be made available and accessible to them and they were able to utilise them credibly, it will give an avenue to boost the production of timber and therefore reduce poverty among the timber producers in the study area.